Preventing The Illegal Trade of Smuggling Small Arms And Light Weapons (SALW) through UNPoA in Indonesia - Ni Gusti Agung Ayu Mas Triwulandari; Putu Eva Ditayani Antari (Yustisia Jurnal Hukum, 2021)
Action is needed to combat the illegal trade of Small Arms and Light Weapons (SALW) because transnational crime is not easy to commit. However, internal conflicts make Indonesia more vulnerable to firearms smuggling, considering its geographical conditions and weak supervision at the border. Consequently, the government cooperates with neighboring countries to maintain national integrity and safety. Also, the government is active in the international regime to deal with illegal trade of SALW through the United Nations Program of Action. This study is legal research by incorporating primary, secondary, and tertiary data. The results showed that Indonesia's position in the United Nations Program of Action helps prevent firearms smuggling and increase capacity-building assistance.Furthermore, the government collaborates with the Ministry of Foreign Affairs and amends and revises Law Number 8 of 1948 concerning Registration and Granting of Permits for the use of Firearms to prevent illegal trade of SALW. In the regional scope, similar collaboration is also conducted with Southeast countries. This is supported by implementing the PoA to Combat Transnational Crime by holding the ASEAN Ministerial Meeting on Transnational Crime (AMMTC). In the international scope, the United Nations Convention Against Transnational Crime and its three protocols were introduced to eradicate the illegal trade of SAWL.